Nutritional status and cardiovascular risk in women with breast cancer - Meneses, Thayanne Breckenfeld; Cunha, Tamires Regina da Silva; Burgos, Maria Goretti Pessoa de Araújo (Mastology, 2020)
Objective: To evaluate the nutritional status and the cardiovascular risk in women with breast cancer and identify factors associated with excessive body weight. Methods: A descriptive, cross-sectional, quantitative study was carried out in an oncology outpatient clinic and, gynecology/oncology wards at the Hospital das Clínicas da Universidade Federal de Pernambuco, from March to August 2019. The data analyzed was related to sociodemographic, gynecologic, clinic, anthropometric and lifestyle factors. Nutritional status was assessed using Body Mass Index, considering excessive body weight when > 25 kg/m2 for adults and > 27 kg/m2 for elderly. Obesity was considered > 30 kg/m 2. Cardiovascular risk was defined by waist circumference (≥ 80 cm), neck circumference (≥ 34 cm) and waist-to-height ratio (> 0.5). Results: A total of 46 patients were included, with a mean age of 51.9 years, and the majority in outpatient follow-up. The population was mostly Caucasian women, who were married or in a civil union, who had had at least one pregnancy, were in menopause, and were sedentary. High frequencies of excessive body weight (76.1%) and obesity (43.5%) were observed, and anthropometric parameters revealed an elevated frequency of cardiovascular risk in this population, waist circumference (97.8%), neck circumference (84.8%), and waist-to-height ratio (95.7%). Unemployment (p = 0.020), and waist (p = 0.001) and neck (p = 0.001) circumferences were statistically associated factors to excessive body weight. Conclusions: The anthropometric profile of women with breast cancer indicated excess body weight and elevated cardiovascular risk, which suggests to the need for nutrition intervention and follow-up after the diagnosis.